Understanding unfolding and refolding of the antibody fragments (Fab). II. Mapping intra and inter-chain disulfide bonds using mass spectrometry - Nainwal, Neeraj; Chirmade, Tejas; Gani, Kayanat; Rana, Sunil; Bhambure, Rahul (Biochemical Engineering Journal, 2022)
Disulfide bond formation in recombinant protein therapeutics has a significant impact on the integrity and biological activity of the drug product. Formation of the disulfide linkage is the key rate-limiting step in in vitro refolding and overall manufacturing of the antibody fragments (Fab). This investigation is focused on mapping the intra, and inter-chain disulfide bonds in the in vitro refolded antibody fragments by using mass spectrometry (MS). Biosimilar rHu Ranibizumab and rHu Certolizumab expressed using E. coli were selected for the study. Both Fabs contain ten cysteine residues leading to two intra-chain disulfide bonds on each subunit and a single interchain disulfide linkage. rHu Certolizumab has an additional cysteine which is unpaired and used for pegylation. The amino acid sequence in the disulfide-bonded peptides was confirmed by Collision-induced dissociation (CID), Electron transfer dissociation (ETD) and High-energy collision dissociation (HCD). The light chain (LC) intra-chain disulfide is formed between Cys23-Cys88 and Cys134-Cys194 in both the Fabs. The heavy chain (HC) intra-chain disulfides are formed between Cys22-Cys96 and Cys150-Cys206 in rHu Ranibizumab. LC and HC subunits of rHu Ranibizumab are covalently linked by disulfide linkage formed between Cys214 of LC and Cys226 of HC. This study suggests that information from multiple MS platforms and orthogonal methods for peptide fragmentation can be effectively used to map disulfide linkages in biosimilar therapeutic proteins.
Keywords: Antibody fragments (Fab); Collision-induced dissociation; Electron transfer dissociation; High-energy collision dissociation; in vitro refolding; Ranibizumab